A new species of acamptopoeum from colombia (hymenoptera: andrenidae: panurginae) (2004)
A new species of the panurginae bee genus Acamptopoeum (Andrenidae:Calliopsini), from a xeric highland area in the Eastern Andes of Colombia is describedand illustrated. Acamptopoeum fernandezi sp. nov., can be recognized by the blackintegument without blue or green reflections and the short, sparse white pubescenceon the body, not forming apical bands of setae on metasoma. A. prinii is alsoreported for the first time for Colombia.